2007
DOI: 10.1007/s10577-007-1161-y
|View full text |Cite
|
Sign up to set email alerts
|

Search for the sex-determining switch in monotremes: Mapping WT1, SF1, LHX1, LHX2, FGF9, WNT4, RSPO1 and GATA4 in platypus

Abstract: The duck-billed platypus has five pairs of sex chromosomes, but there is no information about the primary sex-determining switch in this species. As there is no apparent SRY orthologue in platypus, another gene must acquire the function of a key regulator of the gonadal male or female fate. SOX9 was ruled out from being this key regulator as it maps to an autosome in platypus. To check whether other genes in mammalian gonadogenesis could be the primary switch in monotremes, we have mapped a number of candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…For instance, the unpaired part of X 5 contains the DMRT1 gene that is a candidate for sex determination in birds and for sex reversal in humans; however, it is present in two doses in females and one in males (which is the opposite situation from birds), and therefore is unlikely to play the role of sex-determining switch in platypus (El-Mogharbel et al 2007;Wallis et al 2007). Grafodatskaya et al (2007) demonstrated that GATA4, a gene that interacts with human and mouse male gonad development, lies on the platypus sex chromosomes, but on the Y 1 /X 2 pairing region, and is therefore a poor sexdetermining candidate. Other putative sex-determining genes (genes know to play a role in vertebrate sex determination) lie on autosomes ); thus the hunt for a putative platypus sex-determining switch continues.…”
Section: Platypus Y Chromosomes and Platypus Sex Determinationmentioning
confidence: 99%
“…For instance, the unpaired part of X 5 contains the DMRT1 gene that is a candidate for sex determination in birds and for sex reversal in humans; however, it is present in two doses in females and one in males (which is the opposite situation from birds), and therefore is unlikely to play the role of sex-determining switch in platypus (El-Mogharbel et al 2007;Wallis et al 2007). Grafodatskaya et al (2007) demonstrated that GATA4, a gene that interacts with human and mouse male gonad development, lies on the platypus sex chromosomes, but on the Y 1 /X 2 pairing region, and is therefore a poor sexdetermining candidate. Other putative sex-determining genes (genes know to play a role in vertebrate sex determination) lie on autosomes ); thus the hunt for a putative platypus sex-determining switch continues.…”
Section: Platypus Y Chromosomes and Platypus Sex Determinationmentioning
confidence: 99%
“…DMRT1, the putative sex-determining gene in birds (Smith et al, 2009), is located on platypus chromosome X 5 (Grützner et al, 2004), but it is doubtful that it could be a sex-determining gene in platypus, because it is present in two copies in female and single copy in males, which is opposite to its dosage in chicken (two copies in males). Accordingly, the platypus sex-determining gene remains unknown (Grafodatskaya et al, 2007).…”
Section: Marsupial Sex Chromosomesmentioning
confidence: 99%
“…Interestingly, GATA4 was found to be on the sex chromosomes in the platypus (Ornithorhynchus anatinus) [21]. However, GATA4 is not considered to be a good candidate gene for sex determination in monotremes because it maps to the pairing regions and is present in the same dose in both males and females [21].Although the role of GATA4 in mammalian reproduction has been well demonstrated [22][23][24][25][26][27][28][29], the reproductive functions of GATA4 remain elusive in nonmammalian vertebrates. In the chicken, GATA4 showed no sexual dimorphic expression during sexual differentiation [30,31].…”
mentioning
confidence: 99%
“…While Sf1Cre-mediated excision of Gata4 permitted normal expression of most genes associated with embryonic testis development, gonadal loss of Fog2 resulted in an early partial block in the male pathway and sex reversal. Interestingly, GATA4 was found to be on the sex chromosomes in the platypus (Ornithorhynchus anatinus) [21]. However, GATA4 is not considered to be a good candidate gene for sex determination in monotremes because it maps to the pairing regions and is present in the same dose in both males and females [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation